Monitoring of anthropogenic effects on forest ecosystems within the municipality of Vallières in the Republic of Haiti from 1984 to 2019 - Waselin Salomon (Elsevier, 2021)
The forest resources within the municipality of Vallières in the Republic of Haiti are subject to ever-increasing anthropogenic pressures, leading to a reduction in their area and the degradation of their ecosystem services. This study quantified the spatial pattern changes of forest ecosystems within the municipality of Vallières from 1984 to 2019 using a cartographic approach coupled with landscape metrics. The evolving trend in the landscape within the municipality of Vallières and its sections reveals that in 35 years the area of ​​forests land has diminished through the fragmentation of the large initial patches, as opposed to the progressive dynamics of agricultural and bare land, mainly under strain from the creation and merging of the patches. The underlying causes of the observed landscape dynamics are demographic pressure coupled with the lack of an appropriate program for the preservation of forest resources and improvement of the standard of living conditions of the local population. Our results justify the implementation of strategies to preserve the rare patches of the forests that remain, taking into account the local socio-economic context.